Effectiveness and safety of PD-1/L1 inhibitors as first-line therapy for patients with advanced or metastatic urothelial carcinoma who are ineligible for platinum-based chemotherapy: a meta-analysis - Liang, Weiming; Wang, Zhijing; Huang, Zhilong; Huang, Yanping; Li, Chunyan; Liang, Yiwen; Huang, Miaoyan; Zhang, Duo; Li, Chenchen (Frontiers in Immunology, 2025)
ObjectiveTo evaluate the efficacy and safety of programmed cell death protein 1 or its ligand (PD-1/L1) inhibitors as first-line therapy in advanced or metastatic urothelial carcinoma (mUC) who are ineligible for platinum-based chemotherapy.MethodA systematic search was conducted in four databases (Pubmed, Embase, Web of Science, and the Cochrane Library) to find articles that evaluate the effectiveness of first-line PD-1/L1 inhibitors for mUC, from the establishment of the databases to 22 November 2023. Meta-analyses were performed to evaluate the frequencies of progression-free survival (PFS), overall survival (OS), complete response (CR), partial response (PR), stable disease (SD), progressive disease (PD), objective response rate (ORR), disease control rate (DCR), and grade ≥ 3 treatment-related adverse events (trAEs).ResultsTotally six studies were included for meta-analysis. The CR, PR, SD, PD, ORR, DCR, and grade ≥ 3 trAEs rate were 0.06 [95% confidence interval (CI), 0.04 to 0.07], 0.22 (95% CI, 0.16 to 0.30), 0.27 (95% CI, 0.23 to 0.31), 0.31 (95% CI, 0.20 to 0.44), 0.28 (95% CI, 0.21 to 0.37), 0.57 (95% CI, 0.47 to 0.67) and 0.26 (95% CI, 0.14 to 0.40), respectively. The median PFS and OS were 4.5 months and 13.7 months, respectively. Subgroup analysis showed that PD-1/L1 inhibitors monotherapy had an ORR rate of 0.25 (95% CI, 0.21 to 0.29) and a DCR rate of 0.50(95% CI, 0.44 to 0.56), while PD-1/L1 dual immunotherapy had a better ORR rate of 0.33 (95% CI, 0.15 to 0.52) and a DCR rate of 0.65 (95% CI, 0.49 to 0.80). However, there was no significant difference in PFS and OS between the two groups.ConclusionThe findings indicated that PD-1/L1 inhibitors could be used as a safe and viable first-line treatment option for patients with advanced or metastatic urothelial carcinoma who were not suitable candidates for platinum-based chemotherapy. Specifically, the combination of Enfortumab vedotin (EV) and pembrolizumab (Pembro) showed more effectiveness in treating patients compared to trials using the current standard treatment, suggesting that it could be a promising alternative treatment option.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42024510152.